Mellem kvindekamp og miljøkrise: Økofeminismens indtog i den danske kvindebevægelse - Søby Fogh, Stine (Culture and History: Student Research Papers, 2025)
This article explores the emergence of ecofeminism in 1970s Denmark through a dual focus. First, it analyses two foundational voices — Ninon Schloss and Lis Thorbjørnsen — and their diverging positions on the relationship between gender, nature, and societal change. Second, it explores the public debate in the newspaper Information in 1977 between ecofeminists and other parts of the women’s movement. The study reveals internal ideological differences within ecofeminism as well as its contested status within the broader women’s movement in the 1970s, highlighting ecofeminism’s role as both a feminist critique and a political response to ecological crisis.